Littletodd.com - Lua, Yong Da (2015)
The aim of this project is to design a web portal that caters to parents mostly. It is a one-stop web portal that provides information and services related to babies and toddlers. Some artificial intelligence will be employed to design ‘help’ for the parents as well as customer interactive experience at the web portal. This is the perfect project for you to showcase your creativity and initiatives.